Neonatal Sepsis: A 6-Year Analysis in a Neonatal Care Unit in Taiwan - Jun-Ho Wu; Chien-Yi Chen; Po-Nien Tsao; Wu-Shiun Hsieh; Hung-Chieh Chou (Pediatrics and Neonatology)
Neonatal sepsis is the most serious problem in neonatal intensive care, resulting in significant morbidity and mortality. We evaluated the causative pathogen, drug sensitivity, hematological parameters, clinical course and mortality rate of neonatal sepsis in a Taiwanese medical center and compared our results to those of previous studies conducted in Taiwan. Methods: Neonates admitted to the neonatal intensive care unit (NICU) at National Taiwan University Hospital (NTUH) between January 2001 and December 2006 were included in this study. Patients were divided into early-onset sepsis and late-onset sepsis groups if their culture tested positive within the first 7 days of life or later, respectively. Results: A total of 109 episodes of sepsis were identified in 100 neonates. The incidence of sepsis was 4.06% among all NICU admissions. Most neonates with early-onset sepsis were term infants, while very low birth weight (VLBW) and preterm infants accounted for the majority of cases of late-onset sepsis. In early-onset sepsis, the most common pathogens responsible included group B streptococci (GBS) (36%) and Escherichia coli (E. coli) (26%). GBS was associated with more meningitis involvement but lower incidence of mortality compared with E. coli. The most common causative micro organisms in late-onset sepsis were coagulase-negative staphylococci (CONS) (40%) and Candida (15%). The sepsis-related mortality rates were higher in early-onset sepsis (10%) than in late-onset sepsis (7%). Conclusion: Unlike previous reports from Taiwan, in the present study, GBS was found to be the leading pathogen in early-onset sepsis. GBS screening and intrapartum antibiotic prophylaxis guidelines should be used in Taiwan to prevent early neonatal sepsis. The most common causative microorganisms of late-onset sepsis were CONS and Candida species. Candida parapsilosis was associated with a high mortality rate.